LOCUS OF CONTROL DAN PERILAKU MENYONTEK SERTA IMPLIKASINYA TERHADAP BIMBINGAN DAN KONSELING (Studi pada Siswa Sekolah Menengah Atas Padang Ganting) - Sari, Intan; ., Marjohan; ., Neviyarni (Universitas Negeri Padang, 2013)
The purpose of this research is to reveal the locus of control with the relation to the student’s cheating behavior in grade 10 of high shcool Padang Ganting. This research use a descriptive correlational method. The research is conducted on students in grade 10 high school Padang Ganting 2011-2012.as many as 439 from the populations, samples were taken by using a technique kurtosis sumpling random sample that produce 148 person. The instrument that used in this research is the locus of control scale by Rotter and cheating behavior questionnaire with likert scale and the analyzed using pearson correlation techniques.The research revealed that generally the students have an external locus of control and cheating behavior enough category. Besides, it also found a negative correlation between the score of locus of control and cheating behavior. The implication of this research is an internal locus of control is needed to reduce cheating behavior.